The expression of emotions in the narrative of older adults with mild or moderate cognitive impairment: Metalinguistic analysis and intervention - Mendizábal de la Cruz, Nieves; González Martín, Enrique (Revista de Investigación en Logopedia, 2023)
Emotions are an essential part of human beings throughout all stages of their lives. In this work, we study the expression of emotions in the oral discourse of 23 older adults (16 women and 7 men) between 75 and 95 years old, diagnosed with some cognitive impairment due to various diseases, taken from the corpus "Metalanguage y aging" (Mendizábal, González, Jimeno and Sánchez, 2022). The aim is to describe and analyze the strategies of expression of positive and negative emotions illustrated with examples and to establish the proportion of emotions expressed according to sex and age. The classification of emotions is based on previous studies (Rusell, 2009; Sander, 2013; Lazarus, 2001) but adapted to the type of semi-structured interview for data extraction. The analysis of the expression of emotions in the informants who make up the corpus reveals lexical and grammatical deficiencies that prevent them from expressing their emotions more effectively, especially negative ones. The results obtained from the analysis lead us to the development of a specific speech therapy intervention so that the elderly population with mild cognitive impairment may have a communicative competence that helps them to optimally express their feelings and emotions.
Keywords: Emotions; Language; Mild cognitive impairment; Speech therapy intervention